Thromboxane Generation in Patients with Essential Hypertension or Cerebrovascular Disease and Effect of Oral Aspirin - Matsumoto, M; Nukada, T; Uyama, O; Yoneda, S; Imaizumi, M; Miyamoto, T; Kayama, N (Thrombosis and Haemostasis, 1980)
The ability of platelets to synthesize thromboxane B2 (TxB2) from arachidonic acid (AA) or prostaglandin H2 (PGH2) was studied in 26 control subjects, 40 patients with essential hypertension, 20 patients with cerebrovascular disease (CVD) not taking aspirin and 11 patients with CVD taking aspirin. The activity of platelets to form TxB2 from AA or PGH2 was measured using 1 — 14C arachidonic acid or 1—14C PGH2 as a substrate. There was no significant difference in TxB2 generation from AA or PGH2 among the platelets collected from the control subjects, hypertensive patients and CVD patients not taking aspirin.In CVD patients taking aspirin, marked suppression was observed in TxB2 synthesis from AA, but no suppression in TxB2 synthesis from PGH2. At least 750 mg aspirin per day were required for nearly complete suppression of TxB2 generation from AA.
Keywords: Thromboxane generation; Hypertension; Cerebrovascular disease; Aspirin; Prostaglandin; Platelet